Barbie in the Media
XXV, 377 p. 45 illus., 44 illus. in color.
Keywords: Vibrant and thought-provoking, Barbie in the Media is an exploration of one of our most iconic figures shaping cultural narratives around gender, race, class, and power. The book is full of insight and rich, original analysis of Barbie’s role across film, television, literature, and digital platforms. For scholars, fans, and cultural critics, a must read! -Orly Lobel, author of You Don’t Own Me: How Mattel v. MGA Revealed Barbie’s Dark Side Barbie in the Media offers a comprehensive take on the iconic toy in transmedia form. Imaginative, insightful and offering something entirely new on the globally adored doll, this collection will quickly become the key resource on Barbie for researchers in media studies, toys and children's culture. -Lincoln Geraghty, Ph.D., Professor of Media Cultures, University of Portsmouth, UK What is the significance of Barbie’s journey from toy aisles to screens? Barbie in the Media offers a groundbreaking exploration of Barbie as a transmedia phenomenon. In examining the brand’s multifaceted media presence, this volume’s chapters consider both Mattel’s corporate storytelling about and fans’ reinterpretations of the iconic doll. Collectively, they reveal that these mediated negotiations of Barbie reflect and contribute to broader discourses about gender and identity in evolving sociopolitical contexts—inscribing the doll with ever-changing (and often conflicting) anxieties and dreams. These render the brand’s media presence a fascinating site of contested meaning, worthy of the sustained critique that Barbie in the Media offers readers. Emily R. Aguiló-Pérez is a professor of English (Youth Literatures & Cultures) at West Chester University of Pennsylvania, USA. She has authored and co-edited numerous books and articles, including An American Icon in Puerto Rico: Barbie, Girlhood, and Colonialism at Play (2022); Islas Lectoras: Bibliografía infantil puertorriqueña (2023); and The Cultural Legacy of Disney: A Century of Magic (2024). Rebecca C. Hains is a professor of Media & Communication at Salem State University, USA. She is an author and co-editor of numerous books and articles on children’s media culture, including Growing Up With Girl Power: Girlhood on Screen and in Everyday Life (2012); The Princess Problem (2014); Cultural Studies of LEGO: More than Just Bricks (2019); and Supernatural Youth in Media (2025).